Meningkatkan Kemampuan Kepala Sekolah dalam Menyusun Visi Sekolah Melalui Bimbingan Intensif Pada SMP Negeri 10 Sungai Kakap - Lili Ng Chui Mi (Universitas Tanjungpura, 2015)
This study departs from the principal background in formulating the school's vision not incorporate elements of skill, because there is a deep understanding of the formulation of the school's vision. this can be known when researcher holds managerial supervision by looking at the KTSP documents​​ made, where in chapter II contains the vision of the school. This study aims to improve the ability of principals in formulating the school's vision. The research method used is a form of qualitative descriptive approach. Datas were collected through interviews, observation, and discussion. The implementation procedure consisted of stages: (1) planning, (2) implementation, (3) observation, and (4) reflection. The results showed that through intensive counseling can improve the ability of principals in formulating the school's vision, this can be evidenced from the observation from cycle 1 to cycle 2. Before the guidance, the school's vision reads: